DECENTRALIZATION AS A FACTOR OF DIVERSIFICATION OF DEVELOPMENT OF RURAL TERRITORIES (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The urgency of this study is due to the fact that the process of decentralization is currently the basis for the development of rural territories, as a result of which formed amalgamated hromadas. The purpose of the study is to substantiate the process of decentralization as a factor of diversification of development of rural territories in Ukraine. The article analyzes the existing theoretical approaches to the interpretation of the term «decentralization». It has been determined that decentralization is a complex process that influences the social, economic and environmental spheres of development of rural amalgamated hromadas, as it approximates the processes of governance and decision-making to the public, and thus enables to implement strategies, programs, projects of rural development and provide services that better meet the needs of the region. The main types and forms of decentralization are singled out. Trends in the formation of amalgamated hromadas since the beginning of the reform of local self-government and territorial organization of power in Ukraine are revealed. The necessity of diversification in the field of development of rural territories is grounded in order to expand the spheres of employment and income of the rural population in the conditions of the process of decentralization. The influence of the decentralization process on the development of rural territories is determined. The own definition of the category «diversification of development of rural territories» has been formed. The basic directions of diversification of development of rural territories are singled out. It has been determined that decentralization acts as an factor in stabilizing the socio-economic situation in Ukraine, as it contributes to increasing the efficiency of using budget funds at all levels of government.
Keywords: decentralization, diversification, development of rural territories, AHs, amalgamated hromadas, budget.